Respiration Interacts With Photosynthesis Through the Acceptor Side of Photosystem I, Reflected in the Dark-to-Light Induction Kinetics of Chlorophyll Fluorescence in the Cyanobacterium Synechocystis sp. PCC 6803 - Ogawa, Takako; Suzuki, Kenta; Sonoike, Kintake (Frontiers in Plant Science, 2021)
In cyanobacteria, the photosynthetic prokaryotes, direct interaction between photosynthesis and respiration exists at plastoquinone (PQ) pool, which is shared by the two electron transport chains. Another possible point of intersection of the two electron transport chains is NADPH, which is the major electron donor to the respiratory chain as well as the final product of the photosynthetic chain. Here, we showed that the redox state of NADPH in the dark affected chlorophyll fluorescence induction in the cyanobacterium Synechocystis sp. PCC 6803 in a quantitative manner. Accumulation of the reduced NADPH in the dark due to the defect in type 1 NAD(P)H dehydrogenase complex in the respiratory chain resulted in the faster rise to the peak in the dark-to-light induction of chlorophyll fluorescence, while depletion of NADPH due to the defect in pentose phosphate pathway resulted in the delayed appearance of the initial peak in the induction kinetics. There was a strong correlation between the dark level of NADPH determined by its fluorescence and the peak position of the induction kinetics of chlorophyll fluorescence. These results indicate that photosynthesis interacts with respiration through NADPH, which enable us to monitor the redox condition of the acceptor side of photosystem I by simple measurements of chlorophyll fluorescence induction in cyanobacteria.